Impact of vitamin D on gene expression in Atlantic salmon skin - Lewis D. Taylor; Courtney E. Gorman; Fintan Egan; Neil M. Ruane; Philip McGinnity; C. Darrin Hulsey (PLoS ONE, 2026)
Vitamin D is a crucial micronutrient for vertebrate health that affects musculoskeletal function and likely modulates immune responses in tissues such as the skin. Infectious diseases are a critical concern in Atlantic salmon aquaculture due to the potential economic impact of stock losses, risks to fish welfare, and environmental sustainability. Since the skin is the first line of immunological defence, its ability to mediate host-pathogen interactions may be influenced by dietary vitamin D. This study examined the transcriptomic response of salmon skin after six months of dietary vitamin D supplementation, with an emphasis on immune-related gene expression. A total of 151 differentially expressed genes were identified, 27 of which are linked to inflammation, antigen presentation, and both innate and adaptive immunity. These results indicate that vitamin D could modulate cutaneous immune responses by reducing inflammation and enhancing innate defences, potentially improving resistance to many skin-associated salmon pathogens.